Overview of the discussion "The city as a medium: visual dimensions and modes" - O. Y. Pavlova (Ukrainian Cultural Studies, 2022)
The text of the review does not reproduce all the conflicts and conversations of the meeting, but those that, according to the author, were centered around scientific considerations. The sequence of performances is preserved.